Confessions of a Non‐Designer Designer. (June 2015) - Lee, Mark
<x xml:space="preserve">Abstract</x> The creation of a product design almost always involves competing visions within the team. Business, engineering, and design all have views on what makes for a successful product. News flash: The user should be the winner in that battle. If you are a consumer, you want this human factors engineer to be on the design team.